Comparative Study of Orbital Indices in Human Dry Skulls Obtained from People in Eastern Region of Nepal: Comparative Study of Orbital Indices in Human Dry Skulls Obtained from People in Eastern Region of Nepal - Mallick, Ram L. (International Journal of Pharmaceutical & Biological Archive, 2018)
Aim: The aim of this study is to measure the known variables of orbital indices with utilization of human dry skulls among people in eastern region of Nepal. Materials and Methods: The parameters (such as orbital height [OH], orbital breadth [OB], and orbital index [OI]) were used for comparative analysis of orbital indices in collected skull samples. Based on these morphological features, each human dry skull was categorized into megaseme, mesoseme, and microseme groups. The determination of orbital indices with known parameters (such as OH, OB, and OI) was carried out in next. Results and Discussion: Here, we observed that abundantly 54% of people had OI >89 that had laid us to report that majority of population in this area belongs to the megaseme group. Mesoseme was next to grasp population as 32% of collected skulls were having OI values between 83 and 89. The remaining 14% were set into microseme with OI values <83. We further investigated the pattern of variation in both right- and leftsided OH, OB, and OI, and their findings were peculiar to interestingly report in our study among people residing in this part of the world.